Hypercholesterolemia Is an Associated Factor for Risk of Differentiated Thyroid Cancer in Chinese Population - Zhao, Junyu; Tian, Yutian; Yao, Jinming; Gu, He; Zhang, Rui; Wang, Huanjun; Liao, Lin; Dong, Jianjun (Frontiers in Oncology, 2021)
Background: Hyperlipidemia has been hypothesized as a risk factor for thyroid cancer. However, the association between hypercholesterolemia and thyroid cancer is unclear, especially in Chinese population without available published data. We conducted this study to investigate the relationship between hypercholesterolemia and differentiated thyroid cancer (DTC) in Chinese population. Methods: 3748 patients were enrolled in the study, including 2021 DTC patients and 1727 benign subjects with benign thyroid nodules. Demographic characteristics, medical history and clinical hematological examination were collected. Stratified analyses of association between hypercholesterolemia and risk of DTC were done. Multivariable logistic regression models were used to estimate the association between hypercholesterolemia and the risk of thyroid nodules being malignant. This study protocol was approved by the ethics committee of Shandong Provincial Qianfoshan Hospital and assigned in ClinicalTrials.gov protocol registration and results system (NCT03006289, https://clinicaltrials.gov/ct2/show/NCT03006289). Results: The level of serum total cholesterol in patients with DTC is higher than that in benign subjects (P<0.001). After adjusting hypercholesterolemia, age (P<0.001), triglyceride (P=0.003), and thyroid stimulating hormone (TSH) (P<0.001) are found to be confounding factors. The risk of DTC in patients younger than 45 years old is 2.08 times than that of patients older than 45 years old (odds ratio=0.48, 95% CI (0.38, 0.61), P<0.001). A high TSH level is highly associated with the increased risk of DTC (P<0.001). The multivariable logistic regression analysis revealed that the absence of hypercholesterolemia could reduce the risk of thyroid nodules being malignant (odds ratio=-0.75, 95% CI (-1.39, -0.12), P=0.02). Comparing to the higher level of serum total cholesterol (>5.7 mmol/l), the closer the serum total cholesterol level is to normal (3.17-5.7 mmol/l), the less the risk of thyroid nodules being malignant is, and this difference is statistically significant (odds ratio=-0.67, 95% CI (-1.31, -0.03), P=0.040). However, this difference is not found in the group of patients with lower level of total cholesterol (<3.17 mmol/l, odds ratio=0.43, 95% CI (-1.22, 2.09), P=0.068), suggesting that hypocholesterolemia is not a protective factor in the risk of thyroid nodules being malignant. Conclusions: Hypercholesterolemia is an associated factor for risk of DTC in Chinese population.